MICROORGANISM PATTERN ON NASAL CAVITY OF END STAGE RENAL DISEASE PATIENTS WITH REGULAR HEMODIALYSIS AND STAFFS IN HEMODIALYSIS INSTALLATION ADAM MALIK GENERAL HOSPITAL MEDAN - Imelda Damayanti; Ricke Loesnihari; Syafrizal Nasution (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Colonization is the presence and growth of microorganism on the skin or mucous membrane of the body without any sign of infection. Commonly colonized microorganisms are normal flora within a person's body, but can also be microorganism in the hospital that colonizes within the body a few days after they enter the hospital. The longer a person is hospitalized the more likely to be colonized with the microorganism in the hospital. The objective is to determine microorganism pattern and antimicrobial sensitivity in the nasal cavity of regular hemodialysis patients and staff in Hemodialysis Installation of Adam Malik Hospital Medan. The study was analytic observational with a cross-sectional method, conducted in the Department of Clinical Pathology of Adam Malik Hospital Medan together with Hemodialysis Installation of Adam Malik Hospital Medan from August 2016 - October 2016. The sample was anterior nasal cavity swab which went through identification and sensitivity test. A total number of participants following the study were 46 people where patients and staffs were equal to 23 people. Most bacterial colonization of the nasal cavity of patients and staffs: Staphylococcus epidermidis 9 (39.13%) and 12 (52.17%); Staphylococcus aureus 4 (17.39%) and 3 (13.04%); Staphylococcus saprophyticus 2 (8.70%) and 2 (8.70%). There were 3 MRSA from a total of 23 bacteria (13.04%) in regular hemodialysis patients. MRSA colonization was found in regular hemodialysis patients with 50% sensitivity level of Vancomycin.